PENGARUH IRADIASI DAN PENYIMPANAN SERTA RADIORESISTENSI BEBERAPA BAKTERI PATOGEN PADA MAKANAN OLAHAN ASAL AYAM - Meylani, Vita; Harsojo, Harsojo (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- An experiment has been conducted to know microbes contamination in processed food from chicken e.g meatball, rollade and cornet. The storage time was done for 12 weeks and irradiated with the dose of 0, 3 and 5 kGy. The irradiation was done at a multipurpose panoramic batch irradiator (IRPASENA). Parameter measured are total amount of aerobic bacteria, total amount of coliform, Staphylococcus and Salmonella contamination. The results showed the amount of aerobic bacteria at control were found in the range from 3,3 x 104 and 5,2 x 105 CFU/g, while coliform bacteria from1,0 x 102 and 2,6 x 105 CFU/g. Total amount of Staphylococcus were found in the range from 2,0 x 105 and 4,1 x 105 CFU/g. Storage up to 12 weeks at control showed an increase of those total bacteria. No Salmonella was detected in all samples observed. The initial contamination of all processed food observerd have exceeded allowable limit.The dose of 5 kGy could eliminate the total aerobic bacteria, coliform bacteria and Staphylococcus.Â Keywords: Irradiation, Processed Food, Bacteria